Diversity, Equity, and Inclusivity in Contemporary Higher Education: Connecting the Global and Local Contexts - Tószegi, Zsófia J. (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book: Jeffries, R. (Ed.). (2019). Diversity, Equity, and Inclusivity in Contemporary Higher Education. Hershey, PA: IGI Global. ISSN: 2327-6983